Improving Public Governance: The Relationship among Logistics Management, Transparency and Accountability in the Peruvian Public Sector - Cordova , Lucia Castillo; Lopez , Luis Enrique Galvez; Rodríguez , Víctor Hugo Puican (Journal of Ecohumanism, 2024)
This research addressed deficiencies in logistics management and transparency in the Peruvian public sector, focusing specifically on the municipality studied. The research revealed critical problems in the supplier selection and contracting stages, as well as in the updating of the transparency portal, highlighting the erosion of integrity and fairness in public procurement. The study methodology combined quantitative approaches such as surveys and document analysis, which allowed for a comprehensive and nuanced understanding of the problem. Through data triangulation, detailed insights crucial to the development of effective interventions were obtained. The results highlight a significant correlation between effective logistics management practices and high levels of transparency and accountability. Specific practices within Group 3 are identified that could serve as a model for governance reform. This study not only addresses a gap in the existing literature, but also provides a solid foundation for the development of more effective and transparent public policies. By addressing the shortcomings of logistics management, the study contributed to the empowerment of the civil community and the creation of a more open and fair government, indirectly supporting the goals of environmental sustainability and conservation.